Kebijakan Penertiban Ternak; Tantangan Penerapan Di Kecamatan Palasa - M Syukur; Rusdin Rusdin (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2020)
This research related to the implementation of livestock curbing policy in Parigi Moutong district in Palasa sub-district that have livestock which is roam. This research design was descriptive qualitative design. Technique of data collection by using interview and documentation from informant that chosen by using purposive sampling. The researcher found that the implementation of local regulation about livestock curbing is not doing maximal and consistent. The aspect that cause this policy is not effective, because of lack of socialization of the government of Palasa to the public. Lack of resources that prepared in implementation of this policy, not only equipment resources but also financial resources. The attitude of the authorized official in implementation of this policy seems apathetic, shown by there is no punishment related to the existing rules and standard operational procedures in curbing livestock.